(untitled) (Revista de Artes Marciales Asiáticas, 2025)
Judo performance is inherently complex due to the dynamic interplay of various factors influencing technique execution. This retrospective cohort study examined data on the technical-tactical performance of judo athletes with visual impairments across four Paralympic cycles (London 2012, Rio 2016, Tokyo 2020+1, and Paris 2024), categorized by sex (male and female), using a motor-technical classification system. Data from 718 matches and 1,028 technical performances were analyzed. The association between technique group frequencies and Paralympic Games editions, stratified by sex (male and female) was assessed by independent Chi-square tests. The results revealed that athletes consistently favored Group 1 (techniques with turning action, forward throw, and two supporting feet) and Group 10 (groundwork techniques) for both female (X2 = 52.40, p = 0.002) and male athletes (X2 = 53.97, p = 0.002) across all four Paralympic cycles. These consistent patterns suggest that judo athletes with visual impairments maintain stable technical preferences across cycles, regardless of sex. The findings provide valuable aspects into the technical-tactical performance of judo athletes with visual impairments, highlighting the consistency of technique preferences across multiple Paralympic Games. Coaches can focus on these techniques in training, customizing their approaches to align with the athletes’ strengths and preferences, especially those involving turning actions, forward throws, two supporting feet, and groundwork techniques.